2022
DOI: 10.3390/metabo12100950
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Kynurenine and Its Metabolites in Comorbid Chronic Pain and Depression

Abstract: Chronic pain and depression affect millions of people worldwide, and their comorbidity tends to exacerbate the severity of each individual condition. Intersecting brain regions and molecular pathways could probably explain the unique yet complex bidirectional relationship between these two disorders. Recent studies have found that inflammatory reactions, frequently identified in both chronic pain and depression, stimulate certain enzymes in the kynurenine pathway, while concurrently suppressing others. Kynuren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…There are several factors that could be further researched in relation to this, such as depression, mood, and anxiety levels in cancer patients with chronic pain. Depression and anxiety have been found to affect quinolinic acid levels, as shown in studies by Steiner et al (2011) and Athnaiel et al (2022), which found an association between depression and quinolinic acid levels in the brain.…”
Section: Relationship Between Quinolinic Acid Level and Pain Intensitymentioning
confidence: 85%
“…There are several factors that could be further researched in relation to this, such as depression, mood, and anxiety levels in cancer patients with chronic pain. Depression and anxiety have been found to affect quinolinic acid levels, as shown in studies by Steiner et al (2011) and Athnaiel et al (2022), which found an association between depression and quinolinic acid levels in the brain.…”
Section: Relationship Between Quinolinic Acid Level and Pain Intensitymentioning
confidence: 85%
“…QA, which could be a major contributor to depression, is associated with neuroinflammation, depression, and neurodegeneration. Raised values have been observed together with inflammatory markers in several neurodegenerative diseases [ 10 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines upregulate IDO expression and shunt the tryptophan metabolism toward the inflammatory markers Kyn and QA [ 1 , 3 ]. Kyn is also metabolised to KA, which has been ascribed neuroprotective, anti-inflammatory and diabetogenic effects [ 10 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels and ratios between different metabolites of the KP have been implicated in comorbid chronic pain and depression [ 39 ]. A large meta-analysis of 101 studies elaborated on the shift of TRP metabolism from serotonin to the KP and demonstrated decreased TRP and KYN across major depressive disorder (MDD), bipolar disorder, and schizophrenia [ 40 ].…”
Section: The Metabolic Pathways Of Trp: Kp and Serotonin Pathwaymentioning
confidence: 99%